Discussion on The Technical System Of Protection and Restoration of Historical District - Taking The Protection and Renovation of Qingguo Lane Historic District in Changzhou as An Example - Chen, Gao; Shi, Hu (MAJ - Malaysia Architectural Journal, 2025)
The Qingguo Lane district in Changzhou, situated along the ancient Grand Canal, preserves notable historical structures and the city's traditional essence. It embodies layered historical narratives, constituting a vibrant community. Conservation here addresses intricate challenges, including historical element identification, street pattern analysis, restoration strategy categorization, infrastructure enhancement, structural safety improvement, and fire safety. Based on thorough surveys and assessments of its traditional buildings, the district has developed four clear preservation and renovation strategies with specific application scopes. A compilation of Changzhou's architectural traits and artisanal skills has been created, providing technical guidelines for the city's historical restoration projects. The Qingguo Lane project also spearheads research into adaptive preservation technologies for old buildings, focusing on timber and wall reinforcement, fire safety, and functional adaptability. It seeks effective preventive conservation methods for architectural heritage from a technical perspective.